Community Empowerment at Sukagumiwang Village Elementary School, Sukagumiwang District, Indramayu Regency Using the Mind Mapping Method - Didik Himmawan; Ibnu Rusydi; Dini Syifa Agustina (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
In the world of education, learning methods are very necessary to facilitate the implementation of learning in the form of specific implementation of concrete steps so that an effective learning process occurs to achieve a certain goal, such as positive changes to students. Apart from learning methods, learning media also have an important role in increasing elementary school students' interest in learning, especially in lower classes, because students in lower classes are not yet able to think abstractly, so the material taught by teachers needs to be visualized in a more real or concrete form. One of the student contributions in reducing boredom and increasing students' understanding when learning is the program